PENINGKATAN MOTIVASI SISWA DALAM PEMBELAJARAN SULAMAN BAYANGAN MELALUI MODEL DIRECT LEARNING KELAS X.1 SMAN 1 KECAMATAN LAREH SAGO HALABAN - Efni, Widia; Yasnidawati, Yasnidawati; Ernawati, Ernawati (Journal of Home Economics and Tourism, 2012)
About problem low its student motivation in shadow quilt learning with indicator: pleasantly, are ardour, keen. To the effect research is increase motivates student to make shadow quilt. Observational observational action brazes (PTK) consisting of two cycle each cycles 3 x appointments. Subjek is research is student braze X1 SMAN 1 Lareh Sago Halaban's district, with observation, field note, analisis did by quantitative and kualitatif.Result observationaling to point out that student motivation on leisured indicator in design motif on shadow quilt on i. cycle average percentage 58% at category be, on cycle II. 77% at category high. Are ardour in menciplak motif for veil decoration, on i. cycle average percentage 63% at category be, on cycle II. 81% at category high once. Keen on percentages i. cycle 69% at category be, on cycle II. average becomes 77% at tall category. So student studying motivation average on i. cycle 63% at category be, on cycle II. 78% at tall category, its mean have reached capaian's target exceeds 75%. Conclusion is with model direct learning can increase student motivation in learning makes shadow quilt on veil decoration.